2020
DOI: 10.1155/2020/9451591
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Mucin as Frontline Defense of Mucosal Surfaces against Mycobacterium avium Subsp. hominissuis

Abstract: Mycobacterium avium is a human and animal pathogen that infects the host through the mucosal surfaces. Past work has demonstrated that the bacterium can interact with both the respiratory and gastrointestinal tracts. Those surfaces in the body are covered by a bilayer of a glycoprotein, mucin, which works as a physical barrier and a gel which contains antibacterial and antivirus properties. This current work shows that different strains of M. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(58 reference statements)
0
5
0
Order By: Relevance
“… hominissuis has shown that the bacterium, in contrast to P. aeruginosa and Escherichia coli, prevents the binding of the mucus [28], and that ability is related to structural proteins and lipids of the cell wall. It is plausible that the same can be assumed for M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… hominissuis has shown that the bacterium, in contrast to P. aeruginosa and Escherichia coli, prevents the binding of the mucus [28], and that ability is related to structural proteins and lipids of the cell wall. It is plausible that the same can be assumed for M.…”
Section: Discussionmentioning
confidence: 99%
“…Work with M. avium subsp. hominissuis has shown that the bacterium, in contrast to P. aeruginosa and Escherichia coli, prevents the binding of the mucus [28], and that ability is related to structural proteins and lipids of the cell wall. It is plausible that the same can be assumed for M. abscessus, although work is needed for confirmation, since the M. abscessus cell wall is in many aspects different from the M. avium surface [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are high-molecular-weight glycoproteins composed of a core protein coupled to carbohydrate chains and sulfate groups. They have characteristic amino acid repeats and a Cys-rich domain that has a key role in multimerization and mucus function by forming disulfide bridges [ 117 ]. Acting in the host defense, salivary MUC5B and MUC7 can interact with numerous bacteria such as the Streptococcus species or Pseudomonas aeruginosa and pathogenic fungi such as Candida albicans [ 118 ].…”
Section: Chemical Barrier Proteins In Human Body Fluidsmentioning
confidence: 99%
“…The higher temperature of 85 • C for 90 min ensured no growth on agar or in enrichment broth. This would be a preferable (maximum) temperature to use to minimize the likelihood of adverse effects on the integrity and function of treated PPE, which could otherwise compromise the safety of the wearer Surprisingly, the presence of soil load did not appear to protect M. tb, as no growth was observed at either 75 or 85 • C. While the protein content of the soil load is generally thought to be protective, a study by Belcher et al showed that some mycobacterial strains were unable to bind mucin [51], binding directly with the mucosal epithelium in vivo. In our vitro experiment, it is likely that the presence of mucin provided a moist heat environment, allowing for faster rapid heat exchange and, consequently, more rapid killing.…”
Section: Inactivation Of C Difficile Sporesmentioning
confidence: 99%